Parceria imobiliária em loteamentos urbanos - Queiroz, Pablo Meira (2016)
The real estate market in Brazil, more specifically, the land subdivision sector, created a business model based on partnerships between landowners and developers to implement these real estate developments. Despite the pervasiveness of the business model, the real estate partnerships are yet to be subject of legal regulation. This work will elaborate and debate on the main features of the business model, especially the risk and liabilities allocation, the effects arising out of the authorities’ stance about the tax treatment of the parties to these agreements and the alternative structures employed by the market. At the end, it will point out the reasons why the real estate partnerships subsist in the land subdivision market and suggest certain improvements in the business model.